Formulation of a fermented soup with enhanced nutritional quality: higher resistant starch and protein contents and a reduced glycemic index - Ozkan, Kubra; Ince, Gizem; Salih, Ghizlane; Palombieri, Samuela; Sestili, Francesco; Visioni, Andrea; Koksel, Hamit; Sagdic, Osman (SPRINGER INDIA, 2026)
This research focused on developing functional tarhana soup samples with a lower estimated glycemic index (GI) that are high in resistant starch and beta-glucan, and rich in plant-based protein. Tarhana samples were produced by supplementing with hull-less barley and lentil flours and resistant starch obtained from high-amylose wheat. The color, microbial loads, phenolic contents, antioxidant capacity, and GI values of the tarhana samples were evaluated. RS content increased up to 13.82% in the samples treated with autoclaving cycles, while protein reached 20.75% in lentil-supplemented tarhana, enabling several formulations to be classified as high in protein according to EU regulations. Barley addition enhanced beta-glucan levels to 3.09%. Significant increases were also observed in bioactive compounds of tarhana samples supplemented with resistant starch/barley/lentil flours. The results indicate that high-amylose wheat, barley, and lentils might be used as ingredients in traditional tarhana to obtain products with better functional and nutritional properties.
Keywords: Resistant starch; Plant-based protein; beta-glucan; Glycemic index; Soup; Phenolic compound; DIGESTIBILITY; BARLEY; Food Science & Technology